Integrating UNESCO AI Competences in Maritime English Teaching for Maritime Higher Education Students - Aliya Izet Begovic Yahya; Merry Lapasau; Syahfitri Purnama; Oom Rohmah Syamsudin; Abdulkarimu Yanda (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2026)
Maritime English plays a pivotal role in ensuring safety and operational efficiency in global maritime communication, aligning with International Maritime Organization’s (IMO) standardized linguistic framework. The emergence of Artificial Intelligence (AI) in higher education requires a pedagogical shift from conventional language instruction toward AI-integrated Maritime English learning. The unit of analysis in this study comprises empirical and conceptual research articles, while Scopus and SINTA serve as the primary databases for article retrieval. Additional supporting studies from DOAJ and conference proceedings were included only after relevance screening to broaden contextual coverage. Following a PRISMA-guided review, 48 articles published between 2017 and 2025 were screened, resulting in 22 eligible studies for thematic synthesis. The review critically identifies three major themes: (1) early adoption of AI-supported learning tools such as VR simulators, AI chatbots, and automated feedback systems; (2) limited pedagogical integration of AI competencies into Maritime English curricula; and (3) increasing awareness of ethical AI use in maritime education. The findings reveal that current implementation remains technologically oriented rather than pedagogically grounded, particularly in critical thinking, ethical reasoning, and AI-assisted communication competencies. This study contributes a conceptual framework that synthesizes UNESCO AI competencies with Maritime English pedagogy to support curriculum innovation in maritime higher education, particularly in Indonesia and comparable educational contexts.